Women from rural Guatemala who speak Mayan languages have reduced odds of diabetes, hypertension and obesity - Alajajian, Stephen; Strader, Anahí Venzor; Martin, Yolanda Juarez; Scott, Caitlin; Rohloff, Peter (Frontiers in Public Health, 2025)
IntroductionIndigenous languages are integral to the individual and collective identity of humankind. Health benefits of speaking Indigenous languages have been demonstrated but may also be masked by various forms of linguistic and ethnic discrimination. Guatemala has experienced a significant degree of Mayan language loss and endangerment in recent decades. Recognition of the positive associations between Mayan languages and health may positively influence their trajectory.MethodsWe undertook a cross-sectional analysis of a pre-existing dataset from a clinical population of women from Central and Western Guatemala. We compared prevalence of diabetes, hypertension, obesity and underweight among Mayan- and Spanish-speaking Indigenous women, and among non-Indigenous women. We used multiple logistic regression to estimate adjusted odds ratios for each condition by language preference, controlling for confounding factors.ResultsA total of 10,876 women were included in the analysis. Indigenous speakers of Mayan languages had the lowest prevalence of diabetes, hypertension and obesity, and non-Indigenous women had the highest prevalence of underweight. After controlling for sociodemographic factors, Mayan language preference was associated with decreased odds of diabetes [aOR 0.80, 95%CI (0.67, 0.94)], hypertension [aOR 0.80, 95%CI (0.71, 0.91)] and obesity [aOR 0.82, 95%CI (0.74, 0.90)].DiscussionThe reduced odds of diabetes, hypertension and obesity among women who prefer to speak Mayan languages might be explained by cultural and lifestyle factors that are inextricably tied to Mayan language use. These findings are consistent with several previous studies, although associations between Indigenous languages and obesity have been varied. Our findings strengthen the impetus to maintain the vitality of Mayan languages in Guatemala.